High incidence of lower urinary tract dysfunction in women with recurrent urinary tract infections. Issue 1 (29th August 2019) - Lee, Ping‐Jui; Kuo, Hann‐Chorng
Abstract: The aim of this study was to evaluate lower urinary tract dysfunction (LUTD) in women with recurrent urinary tract infections (UTIs). One hundred consecutive female patients with recurrent UTIs who underwent videourodynamic study (VUDS) were included. Another 25 women free from recurrent UTIs served as controls. All the underlying diseases, urine analysis and culture results, VUDS findings, and treatment outcomes of voiding dysfunction were carefully reviewed and analyzed. The mean age of the recurrent UTIs patients was 64.0 ± 16.0 years. Storage and voiding dysfunctions were found in 90 (90%) patients, including bladder neck dysfunction in 19 (19%), detrusor hyperactivity with impaired contractility in 6 (6%), detrusor overactivity in 5 (5%), detrusor underactivity in 10 (10%), dysfunctional voiding in 25 (25%), hypersensitive bladder in 6 (6%), and poor relaxation of the pelvic floor muscle in 20 (20%). Only 10 (10%) patients had normal urodynamic tracings. Compared with the controls, the recurrent UTI patients had significantly smaller cystometric bladder capacity, lower maximum flow rate, smaller voided volume, higher detrusor pressure, and larger PVR volume. However, only 6 (11.3%) patients with recurrent UTIs were free from subsequent UTIs following individualized treatment for their voiding dysfunction. A high incidence of vide urodynamic LUTD was identified in women with recurrent UTIs. Despite receiving individualized treatments based on their VUDS findings, only a small portion of these patients were subsequently free from UTIs.